2011
DOI: 10.1289/ehp.1103741
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Methylmercury Exposure Immunotoxicity among Fish Consumers in Amazonian Brazil

Abstract: Background: Mercury (Hg) is a ubiquitous environmental contaminant with neurodevelopmental and immune system effects. An informative biomarker of Hg-induced immunotoxicity could aid studies on the potential contribution to immune-related health effects.Objectives: Our objectives were to test the hypothesis that methylmercury (MeHg) exposures affect levels of serum biomarkers and to examine interactions between Hg and selenium (Se) in terms of these responses.Methods: This cross-sectional epidemiological study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 41 publications
1
60
1
5
Order By: Relevance
“…IL-2, TNF-α and IFN-γ are all Th1 type cytokines, while IFN-γ, a pro-inflammatory cytokine, can help target cells generate various chemotactic factors to relieve the inflammatory response 27 28. TNF-α is a pleiotropic cytokine critical for inflammation, lymphoid neogenesis, and host defence against various pathogens, and plays multiple roles in the induction of cytokines IL-1, IL-6 and IL-8, and the activation of macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2, TNF-α and IFN-γ are all Th1 type cytokines, while IFN-γ, a pro-inflammatory cytokine, can help target cells generate various chemotactic factors to relieve the inflammatory response 27 28. TNF-α is a pleiotropic cytokine critical for inflammation, lymphoid neogenesis, and host defence against various pathogens, and plays multiple roles in the induction of cytokines IL-1, IL-6 and IL-8, and the activation of macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Metals such as mercury have been associated with antinuclear antibody and inflammatory cytokine production in some exposed individuals. 52 The one published study to date of occupational and avocational metal exposures in SLE cases compared to controls found that exposure to mercury in the occupational setting at least once per week was associated with a modestly (but not significantly) higher risk of SLE (OR 3.1; 95% CI 0.8 – 12.7). 28 Exposure to five or more days of stained or leaded glass as a hobby was also more common among SLE cases than controls, but the rarity of these exposures led to an imprecise effect estimate (OR 3.0; 95% CI 0.8 – 11.6).…”
Section: Less Established Environmental Risk Factorsmentioning
confidence: 99%
“…MeHg is readily taken up by fish through trophic webs, consequently bioaccumulating and biomagnifying into the top predating fish, in addition to fisheating birds, and wild mammals (Gochfeld 2003). This makes fish consumption the primary source of Hg exposure in the general population (Nyland et al 2011;Schaefer et al 2014). In New Jersey, USA, one third of the sampled saltwater fish species were found to have concentrations of Hg above 0.5 ppm, which pose a human health risk for consumers (Burger and Gochfeld 2011).…”
Section: Introductionmentioning
confidence: 99%